Phosphorus sources, filter cake and microorganisms on the morphometric variables in tomato seedlings - Diaz Aguila, Ivis; Castellanos Gonzalez, Leonides; Sarduy Diaz, Mairely; Toledo Vazquez, Layda; Silva Campos, Cid Naudi [UNESP]; Mello Prado, Renato de [UNESP]; Parets Selva, Enrique; Rossato Moda, Leandro [UNESP] (Univ Central Marta Abreu Las Villas, 2016)
The present work aims to evaluate the effect of three phosphorus sources, filter cake and microorganisms on the morphometric variables in tomato seedlings (Solanum lycopersicum L.). The investigation was carried out under greenhouse conditions in the Citrico Arimao Enterprise. A Brown soil without carbonate differentiation was used, to which was carried out an agrochemical analysis previously. An experimental design totally randomized was used, with factorial arrangement 3 x 3 + 1, and three repetitions. As a source of phosphorous triple superphosphate, simple superphosphate and a natural phosphoric rock were used and the three levels of organic fertilization consisted of the application of filter cake, filter cake enriched with Azotofos biofertilizer and without filter cake. At 45 and 60 days, the morphometric variables, height, diameter of the stall, the mass of the aerial part and of the root were measured. Variance analyses for all the variables were carried out. The media were compared by Tukey test with a level of error probability of 5 %. The ASISTAT statistical package was used. The morphometric variables, height, diameter of the stall, fresh mass of the aerial part and roots of the tomato seedlings at 45 and 60 days increased with the addition of filter cake, enriched or not, and the application of the phosphoric rock.
Keywords: organic fertilizer; phosphate fertilizer; microorganisms; seedlings; Solanum lycopersicum